An outpatient clinical study of dissociative disorder not otherwise specified - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2014)
The relatively high prevalence of the diagnosis of dissociative disorder not otherwise specified is frequently considered to be disproportionate. The disproportionate rate of this diagnosis is thought to be related to nosologic and/or diagnostic issues in dissociative identity disorder. We sought to investigate and compare the symptom patterns of these two clinical entities. We conducted a cross-sectional study involving 1314 participants who were screened with the Dissociative Experience Scale (DES) and the Somatoform Dissociation Questionnaire (SDQ). Of the participants, 272 who scored above the cut-off points for the screening questionnaires (DES score > 30 and/or SDQ score > 40 points) were invited to complete a structured interview using the Dissociative Disorders Interview Schedule (DDIS); of this subsample, only 190 participants agreed to participate in the second phase of the study. The mean score for the DES was 18.55 +/- 17.23, and the mean score for the SDQ was 30.19 +/- 13.32. Of the 190 participants, 167 patients were diagnosed as having a dissociative disorder (87.8%). We found that DD-NOS was the most prevalent category of dissociative disorder. There was a significantly larger percentage of patients in the DID group than in the DD-NOS group according to secondary features of DID and Schneiderian symptoms. The secondary features of DID and Schneiderian symptoms appeared to be more specific for DID, while no differences were detected between DID and DD-NOS based on most of the items on the SCL 90R. Further longitudinal studies are needed to determine the features that are similar and dissimilar between DD-NOS and DID. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: STRUCTURED INTERVIEW; IDENTITY DISORDER; PREVALENCE; FREQUENCY